Photoredox catalysis enabling decarboxylative radical cyclization of γ,γ-dimethylallyltryptophan (DMAT) derivatives: formal synthesis of 6,7-secoagroclavine - Regni, Alessio; Bartoccini, Francesca; Piersanti, Giovanni (Beilstein Journal of Organic Chemistry, 2023)
An unusual photoredox-catalyzed radical decarboxylative cyclization cascade reaction of γ,γ-dimethylallyltryptophan (DMAT) derivatives containing unactivated alkene moieties has been developed, providing green and efficient access to various six-, seven-, and eight-membered ring 3,4-fused tricyclic indoles. This type of cyclization, which was hitherto very difficult to comprehend in ergot biosynthesis and to accomplish by more conventional procedures, enables the synthesis of ergot alkaloid precursors. In addition, this work describes a mild, environmentally friendly method to activate, reductively and oxidatively, natural carboxylic acids for decarboxylative C–C bond formation by exploiting the same photocatalyst.
Keywords: decarboxylative cyclization; DMAT; ergot alkaloids; photoredox catalysis; radicals